the substitution method to solve the system 2x+2y=6 , 3x+2y=9 .(1 point

1 answer

First, we will solve one of the equations for either x or y in terms of the other variable. Let's solve the first equation for y:

2x + 2y = 6
2y = 6 - 2x
y = 3 - x

Now, we will substitute this expression for y into the second equation:

3x + 2(3 - x) = 9
3x + 6 - 2x = 9
x + 6 = 9
x = 3

Finally, substitute the value of x back into the first equation to solve for y:

2(3) + 2y = 6
6 + 2y = 6
2y = 0
y = 0

So, the solution to the system of equations is x = 3 and y = 0.
Similar Questions
  1. Solve this system using the substitution method.a – 4b = 2 5a = 3b – 7 Solve using the substitution method and be sure to
    1. answers icon 2 answers
  2. Solving Simultaneous Equations Using Substitution PracticeComplete this assessment to review what you’ve learned. It will not
    1. answers icon 1 answer
  3. Solving Simultaneous Equations Using Substitution Quick Check4 of 54 of 5 Items Question Which of the following uses the
    1. answers icon 1 answer
  4. To solve this system, you could do the following steps:3x+4y=48 6x+2y=60 1. Choose the best method to solve by looking at the
    1. answers icon 7 answers
more similar questions